2009
DOI: 10.1029/2008jd011480
|View full text |Cite
|
Sign up to set email alerts
|

Elemental carbon distribution in Svalbard snow

Abstract: [1] The concentration of apparent elemental carbon (EC a , based on a thermal-optical method) in the snow was investigated in Svalbard (European Arctic) during spring 2007. The median EC a concentration of 81 samples was 4.1 mg l À1 and the values ranged from 0 to 80.8 mg l À1 of melt water. The median concentration is nearly an order of magnitude lower than the previously published data of equivalent black carbon (BC e , based on an optical method), obtained from Svalbard snow in the 1980s. A systematic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(139 citation statements)
references
References 46 publications
8
129
2
Order By: Relevance
“…The values we obtain for Svalbard, with medians 7-20 ng g −1 , are higher than those obtained by Forsström et al (2009) using the TO method. Their median for 81 samples across Svalbard was 4 ng g −1 .…”
Section: Norway and Svalbardmentioning
confidence: 46%
See 1 more Smart Citation
“…The values we obtain for Svalbard, with medians 7-20 ng g −1 , are higher than those obtained by Forsström et al (2009) using the TO method. Their median for 81 samples across Svalbard was 4 ng g −1 .…”
Section: Norway and Svalbardmentioning
confidence: 46%
“…Snow on the Greenland Ice Sheet is the cleanest snow of the Arctic, and these values represent the free tropospheric BC content at an elevation of ∼2600 m, so it is of interest to examine evidence from lower-elevation sites where only seasonal snow, rather than ice cores, is available. BC in the near-surface atmosphere has been monitored continuously since 1989 at Alert on Ellesmere Island (82.4 • N, 62.3 • W, 210 m) (Gong et al, 2010), and at Barrow, Alaska (Sharma et al, 2006), and since 1998 at the Zeppelin station above Ny-Ålesund (79 • N, 12 • E, 474 m) (Eleftheriadis et al, 2009;Forsström et al, 2009). All three locations document the seasonal cycle with BC concentrations peaking in winter, and all three show a multi-year decline of the wintertime peak.…”
Section: Has the Arctic Snow Become Cleaner Since 1984?mentioning
confidence: 99%
“…As black carbon (BC) effectively absorbs visible radiation, it causes acceleration in the growth of snow grains, and therefore an overall decrease in albedo. In particular, Hansen et al (2005) suggested that the effect of BC on snow albedo contributes substantially to rapid warming and sea ice loss in the Arctic, although recent measurements (Forsström et al, 2009(Forsström et al, , 2013Doherty et al, 2010) have shown substantially lower levels of BC than was observed in the 1980s (Clarke and Noon, 1985). In view of these findings, parameterizations of BC and soot concentration in snow have been recently developed (Flanner and Zender, 2006;Yasunari et al, 2011;Aoki et al, 2011).…”
Section: Aerosol Deposition On Snow and Icementioning
confidence: 99%
“…This method is commonly used for the analysis of filter-based aerosol samples (Birch and Cary 1996) and it has been used to measure EC in precipitation (Hadley et al 2007;Forsstrom et al 2009;Cerqueira et al 2010). The method applied to rainwater analysis required the filtration of liquid and the collection of particulate carbon on quartz fiber filters, which are the only filters that can withstand the high temperatures of the TOA.…”
Section: Thermal-optical Analyzermentioning
confidence: 99%